2022
DOI: 10.1007/s11104-022-05577-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing chemical environment on physical properties of maize root mucilage

Abstract: Aims High viscosity, low surface tension and hydrophobicity are specific properties of maize root mucilage which contribute to modulate the spatial configuration of the liquid phase in soil pores. Several processes in the rhizosphere, in particularly nutrient absorption, root exudation and microbial activity, may cause strong temporal variations in the chemistry of the soil solution of the rhizosphere. Although the physical properties of maize root mucilage have been repeatedly measured in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Similarly, the adaptation to atmospheric drought-stomatal sensitivity-is a fast, reversible process; on the other hand, mucilage properties are properties expressed over an individual's entire life stage as its function is manifold, for example, for belowground biotic and abiotic interactions (el Zahar Haichar et al, 2014). Although mucilage properties and stomatal sensitivity represent adaptations to two different environmental phenomena, we found a relationship between contact angle, viscosityboth of them important properties for mucilage's behavior during drying and rewetting cycles (Ahmed et al, 2016;Kaltenbach et al, 2018;Knott et al, 2022)-and stomatal sensitivity to increased VPD. As stomatal regulation controls the current transpirational water loss, the plant indirectly affects the speed of soil drying and ultimately delays the drying out of mucilage.…”
Section: Relation Between Mucilage Stomatal Sensitivity and Environme...mentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, the adaptation to atmospheric drought-stomatal sensitivity-is a fast, reversible process; on the other hand, mucilage properties are properties expressed over an individual's entire life stage as its function is manifold, for example, for belowground biotic and abiotic interactions (el Zahar Haichar et al, 2014). Although mucilage properties and stomatal sensitivity represent adaptations to two different environmental phenomena, we found a relationship between contact angle, viscosityboth of them important properties for mucilage's behavior during drying and rewetting cycles (Ahmed et al, 2016;Kaltenbach et al, 2018;Knott et al, 2022)-and stomatal sensitivity to increased VPD. As stomatal regulation controls the current transpirational water loss, the plant indirectly affects the speed of soil drying and ultimately delays the drying out of mucilage.…”
Section: Relation Between Mucilage Stomatal Sensitivity and Environme...mentioning
confidence: 76%
“…These high contact angles, causing a hydrophobic surface of mucilage, can be caused by differences in mucilage chemical composition, the amphiphilic nature of mucilage composing polymers and the amount of cations (Knott et al, 2022). Mucilage with high contact angles often contains more phospholipids than those with a lower contact angle.…”
Section: Mucilage Propertiesmentioning
confidence: 99%
“…[ 36 ] Also, wettability of dried mucilage generally increased with increasing viscosity, with highest significance for Dia samples (Figure 4c, d, Figure S4e) suggesting that the reduced mobility of surface‐active substances mitigated a surface hydrophobization during drying. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…[36] Also, wettability of dried mucilage generally increased with increasing viscosity, with highest significance for Dia samples (Figure 4c, d, Figure S4e) suggesting that the reduced mobility of surface-active substances mitigated a surface hydrophobization during drying. [37] 4. stable network. This dense network results in higher viscosity, leading to reduced mobility of surface-active substances and ions, which contributes to higher surface tension and lower EC compared to root mucilage.…”
Section: Substance Exchange Is Hindered By Cationic Cross-linksmentioning
confidence: 99%
“…The potential role of mucilage for water uptake at the pore scale is addressed in case study four by Schnepf et al (2022), demonstrating that the interaction between mucilage, water and soil particles increases the connectivity of the liquid phase across the rhizosphere. Knott et al (2022) add to this topic, establishing how physical properties of mucilages change with pH and the presence of divalent cations. Furthermore, Werner et al (2022) have shown that not only the chemical environment changes the mucilage properties, but that mucilage composition strongly depends on the growth conditions, the collection system and the age of the plant.…”
Section: Rhizosphere Traits and Water Uptakementioning
confidence: 99%